Effect of Placental Therapy on Hemodynamics in Maternal–Placental–Fetal System and Delivery Outcome in Pregnants with Diabetes mellitus Type 1 - Lutsenko, N. S.; Evtereva, I. A.; Prokopyuk, O. S.; Geraskina, L. R. (Problems of Cryobiology and Cryomedicine, 2008)
The heterotopic injection of cryopreserved placental tissue to 19 pregnanty women with Diabetes mellitus has been carried out. The positive effect of placental tissue on Diabetes mellitus, functional condition of fetoplacental complex and delivery outcome has been verified.